Applied electronics: useful for mechanical,automobile,fabrication,industrial and production engineering and technology - Jadhav, Tushar R (Everest Publishing House, 2008)
Applied electronics: useful for mechanical,automobile,fabrication,industrial and production engineering and technology / Jadhav, Tushar R. -- Pune: Everest Publishing House, 2008 621.381 J61 No. of Copies : 1